Vitamin D Status of the British African-Caribbean Residents: Analysis of the UK Biobank Cohort - Rebecca M. Vearing (MDPI AG, 2021)
The vitamin D status of the United Kingdom (UK) African-Caribbean (AC) population remains under-researched, despite an increased risk of vitamin D deficiency due to darker skin phenotypes and living at a high latitude. This cross-sectional study explored the vitamin D status and intake of AC individuals (n = 4046 with a valid serum 25(OH)D measurement) from the UK Biobank Cohort, aged ≥40 years at baseline (2006–2010). Over one third of the population were deficient (<25 nmol/L), 41.1% were insufficient (25–50 nmol/L) and 15.9% were sufficient (>50 nmol/L). Median (IQR) 25(OH)D was 30.0 (20.9) nmol/L. Logistic regression showed that brown/black skin phenotype, winter blood draw, not consuming oily fish and not using vitamin D supplements predicted increased odds of vitamin D deficiency, whilst older age and a summer or autumn blood draw were significantly associated with reduced odds of vitamin D deficiency. Vitamin D deficiency and insufficiency were prevalent in this AC population and is of considerable concern given the individual and societal implications of increased morbidity. Public health messaging for this group should focus on year-round vitamin D supplementation and increasing intakes of culturally appropriate vitamin D-rich foods. These data also support the urgent requirement for a revised vitamin D RNI for ethnic groups.